The Interrelation between Corporate Governance Practises and the Financial Performance of Microfinance Institutions in CEMAC - Bin, Anyekezeh Kum-Ngong (Advances in Social Sciences Research Journal, 2024)
This study aims to examine the relationship between corporate governance tools—specifically board size, board gender diversity, capital structure, ownership structure, and audit—and financial performance of microfinance institutions as measured by Return on Assets (ROA) and Operational Self-Sufficiency (OSS). Quantitative data is employed to identify the relationship between the variables. A dataset comprising forty-four microfinance institutes extracted from the Mix Market database for the period 2000 to 2021 is utilised. The research identified correlations between Microfinance Institutions’ financial performance and their board characteristics, capital structure, ownership structure and audit. The exploratory variables all produced significant results. The study identified significant relationships between the examined Corporate Governance practices and the financial performance of microfinance institutions in CEMAC. Capital structure positively influences the ROA and the constructed financial performance index but negatively influences the OSS of microfinance institutions in CEMAC when ownership structure is accounted for and audit is not accounted for. Ownership structure (those which have NGO and NBFI forms) positively influences the ROA and the constructed financial performance but negatively influences the OSS of microfinance institutions to a significant extent. Constructed board characteristics index (board size and board gender diversity) positively influences the ROA and the constructed financial performance index but negatively influences the OSS of microfinance institutions in CEMAC when ownership structure is accounted for and audit is not accounted for. Microfinance size has a positive effect on ROA and OSS but a negative one on the computed finance performance index. When audit is accounted for excluding ownership structure, we conclude that capital structure positively influences the OSS and the constructed financial performance index but negatively influences the ROA of microfinance institutions in CEMAC. The constructed board characteristics index (board size and board gender diversity) positively influences the OSS and the constructed financial performance index but negatively influences the ROA of microfinance institutions in CEMAC when audit is accounted for and ownership structure not. Being audited by large firms leads to a decrease in OSS, an increase in ROA and a general decrease in the constructed financial performance index in microfinance institutions in CEMAC when ownership structure is not considered. This study highlights the significance of corporate governance tools and their effectiveness in the success of organizations.